Penyuluhan teknik budidaya ikan dalam keramba di Desa Sungai Sorik Kecamatan Kuantan Hilir Seberang Kabupaten Kuantan Singingi - Ridwan Manda Putra; Sukendi Sukendi; Yusni Ikhwan Siregar; Lilis Kurnia; Ade Yulindra (PELANTAR PRESS, 2021)
The objectives of the extention were to find out the alternative income generation and empowering of local people by combinely multiused of the lake for fish cageculture, ecotourism attraction. The local people should actively enrolle in promoting existing ecotourism. A introductory survey were done to obtain strategic issue on the local people dealing with the use of Danau Timbang Bunga Pengantin. Apparently, the responce of local people were high during the extention. The audience inquiries wer high and they were intreractive and get to know on the topic of multiuse of lake. Evaluation score showed that 30% of participants obtain very good understand on the topic, while others good (43.3 %) and 20% fair. Therefore, the achievement of the extention categorized good. In summary, the understanding of the participants on the materials appeared good. Further extention were need in terms of the impact on the field.